Innovative China : New Drivers of Growth - World Bank Group (Washington, DC: World Bank, 2019)
After more than three decades of average annual growth close to 10 percent, China's economy is transitioning to a 'new normal' of slower but more balanced and sustainable growth. Its old drivers of growth -- a growing labor force, the migration from rural areas to cities, high levels of investments, and expanding exports -- are waning or having less impact. China's policymakers are well aware that the country needs new drivers of growth.